Unifying complexity science and machine learning - Krakauer, David C. (Frontiers in Complex Systems, 2023)
Complexity science and machine learning are two complementary approaches to discovering and encoding regularities in irreducibly high dimensional phenomena. Whereas complexity science represents a coarse-grained paradigm of understanding, machine learning is a fine-grained paradigm of prediction. Both approaches seek to solve the "Wigner-Reversal" or the unreasonable ineffectiveness of mathematics in the adaptive domain where broken symmetries and broken ergodicity dominate. In order to integrate these paradigms I introduce the idea of "Meta-Ockham" which (1) moves minimality from the description of a model for a phenomenon to a description of a process for generating a model and (2) describes low dimensional features – schema – in these models. Reinforcement learning and natural selection are both parsimonious in this revised sense of minimal processes that parameterize arbitrarily high-dimensional inductive models containing latent, low-dimensional, regularities. I describe these models as "super-Humean" and discuss the scientic value of analyzing their latent dimensions as encoding functional schema.